Tropical Plant Species and Technological Interventions for Improvement 2023
DOI: 10.5772/intechopen.104624
|View full text |Cite
|
Sign up to set email alerts
|

Papaya: The Versatile Tropical Fruit

Abstract: Papaya (Carica papaya L) is a versatile tropical fruit with its usage ranging from consumption, cosmetics, to pharmaceuticals. In 2020, it was the third most-produced tropical fruit crop in the world. Papaya is a trioecious herbaceous plant with distinct flower and fruit morphological appearances. The fruits from hermaphrodite papaya are favorable for both consumption and processing due to their superior quality. Papaya has a genome size of 372 Mb and chromosome of 2n =18. The male and hermaphrodite papaya hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Some authors reported good efficiency in a similar male-specific marker (PMSM1) in male-to-hermaphrodite sex reversal events (Liao et al 2017, Pirovani et al 2018, confirming their male specificity. Moreover, this marker serves dioecious varieties of papaya, leaving aside that papaya fruit production is mainly based on gynodioecious cultivars (Burns et al 2022).…”
Section: Jg áVila-hernández Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported good efficiency in a similar male-specific marker (PMSM1) in male-to-hermaphrodite sex reversal events (Liao et al 2017, Pirovani et al 2018, confirming their male specificity. Moreover, this marker serves dioecious varieties of papaya, leaving aside that papaya fruit production is mainly based on gynodioecious cultivars (Burns et al 2022).…”
Section: Jg áVila-hernández Et Almentioning
confidence: 99%
“…Papaya (Carica papaya L.) is one of the most produced fruits worldwide. Although native to America, it is cultivated in tropical and subtropical areas of several countries such as India, the Dominican Republic, Brazil, Mexico, and Indonesia (Jiménez et al 2014, Burns et al 2022. Its nutritional composition is an added value for consumption due to providing vitamins, minerals, and antioxidants (Mehdipour et al 2006, Santana et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Major papaya producing countries are India, Brazil, Nigeria, Indonesia and Mexico. Average global papaya yield was 29 tonnes/hectare while average yield of top four papaya producing countries was double of the global average [1,2]. Narrow gene pool of C. papaya (one species only) makes it vulnerable to many diseases [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria is the largest producer of papaya in Africa and one of the top five producers of this fruit in the world. [ 8 , 9 ] The papaya is considered a food rather than a source of medicaments in Nigeria.…”
Section: Introductionmentioning
confidence: 99%